On the Assessment of Tribosystem Compatibility by Diverse Indicators and Methods (To the 100th anniversary of N. A. Bushe) - S. M. Zakharov; I. G. Goryacheva (Вестник Научно-исследовательского института железнодорожного транспорта)
The article is devoted to the overview of the indicators (criteria) of tribosystem compatibility proposed by N..Bushe and their further development. Temperature criterion of compatibility and response of the tribosystem to tightening of the friction modes characteristic for running in regime are described. Materials compatibility indices and ways to manage surface fatigue mode of wear were considered. The article describes compatibility indices based on the entropy-energy approach, their application to kinematic pairs, the methods for determining such indices and the requirements for lubricating materials, providing compatibility conditions on the proposed indicators. The criteria of compatibility associated with squeeze of the soft structural component of the antifriction alloy materials were considered. The analytic modes that takes into account squeezing of the soft phase of the aluminum alloy not only due to the plastic, but also to the elastic deformation of the matrix are referred. On the basis of calculations based on these models conclusions on the structural composition of the studied alloys and the properties of its components, providing increase in the thickness of the lubricant film in different modes of friction. The results of these calculations based on the average thickness of the soft phase on the yield strength of the matrix and the concentration of the soft phase. are given. Considered comprehensive indices of compatibility with respect to complex tribosystems such as “crankshaft-its bearings” of diesel engines system.